2011
DOI: 10.1007/s10561-011-9257-1
|View full text |Cite
|
Sign up to set email alerts
|

Fresh-frozen human bone graft to repair defect after mandibular giant follicular cyst removal: a case report

Abstract: The purpose of this article is to report the clinical, radiographical and histological findings about a case of a young woman affected by a mandibular giant follicular cyst. Conservative tumor resection was followed by immediate reconstructive treatment using fresh frozen human bone graft, instead of autologous bone graft, as material for bone regeneration. Follicular cyst is a benign, non invasive lesion with slow but progressive growth. Radiological and histological examination of the lesion confirmed the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…8,13,14,17,18 The results were supported by observations showing the osteoinductive and osteoconductive properties of FFB 17,19 and the preservation of bone morphogenetic proteins. Some literature data reported that FFB could be used alone or in combination with autologous bone graft for alveolar bone reconstruction and for large mandibular reconstructions after the resection of a large portion of the mandible for the complete removal of cysts and tumors.…”
Section: Introductionmentioning
confidence: 58%
“…8,13,14,17,18 The results were supported by observations showing the osteoinductive and osteoconductive properties of FFB 17,19 and the preservation of bone morphogenetic proteins. Some literature data reported that FFB could be used alone or in combination with autologous bone graft for alveolar bone reconstruction and for large mandibular reconstructions after the resection of a large portion of the mandible for the complete removal of cysts and tumors.…”
Section: Introductionmentioning
confidence: 58%
“…The absence of negative reports concerning its antigenicity and reduced immunologic reaction in experimental models suggests that FFB could represent an adequate alternative to AB (Okada et al1990;Stevenson et al 1997 studies about the effect of FFB in oral and maxillofacial surgery are scarce. Some literature data reported that FFB could be used alone or in combination with AB for the reconstruction of atrophic alveolar bone or large mandibular defects (Perrott et al1992;D'Aloja et al 2008D'Aloja et al , 2011Franco et al 2009;de Macedo et al 2009;Orsini et al 2011;Acocella et al 2012;Albanese et al 2012). The results were supported by observations showing the osteoinductive and osteoconductive properties of FFB (Perrott et al 1992;Shand et al 2002) and the preservation of bone morphogenetic proteins (Rodella et al 2010).…”
Section: Discussionmentioning
confidence: 94%
“…; Albanese et al. ). The results were supported by observations showing the osteoinductive and osteoconductive properties of FFB (Perrott et al.…”
mentioning
confidence: 98%
“…Among various sources of mesenchymal stem cells, dental pulp is a promising source of osteoprogenitor cells for regenerative medicine [6,7]. Human dental pulp stem cells (hDPSCs) were found to be multipotent with a high osteogenic potential compared to bone marrow mesenchymal stem cells (BMSCs) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The resorption rates of synthetic bone-graft materials depend on the surface area, physical properties, and chemical composition [6]. Calcium sulfate, β-tricalcium phosphate (β-TCP), and hydroxyapatite are typical commercial bone grafts, which exhibit respective resorption periods of 1-2, 6-12, and 12-36 months, respectively [14,16].…”
Section: Introductionmentioning
confidence: 99%